163k views
1 vote
Use the technique of completing the square to transform the quadratic equation into the form (x + c)2 = a.

10x2 + 80x + 220 = 0

Select the best answer from the choices provided

2 Answers

5 votes

Answer:

f(x) = 10 [ (x + 4)^2 = -6 ]

Explanation:

Please use " ^ " to indicate exponentation. Thanks.

Also, please share the possible answer choices. "Select the best answer from the choices provided."

Start with f(x) = 10x^2 + 80x + 220 = 0

Factor out the 10 to simplify this "completing the square."

f(x) = 10(x^2 + 8x + 22) = 0

Complete the square of x^2 + 8x + 22 only, for now.

Identify the coefficient of the x term. It is 8. Take half of that (it is 4) and square your result: 16

Now add 16 to x^2 + 8x and then subtract 16 from that sum:

x^2 + 8x + 16 - 16 + 22 = 0, or

x^2 + 8x + 16 + 6 = 0

Rewrite x^2 + 8x + 16 as (x + 4)^2

and then the whole expression x^2 + 8x + 16 - 16 + 22 as (x + 4)^2 = -6

Finally, rewrite this as

f(x) = 10 [ (x + 4)^2 = -6 ] which is the desired form of the original equation.

User Akka Jaworek
by
5.8k points
1 vote

Answer:

The answer is


(x+4)^2=-6

Explanation:

Follow the steps below.

1) Take common factor 10


10(x^2 + 8x + 22) = 0

2) For an equation of the form
ax ^ 2 + bx + c

Calculate
((b)/(2))^2

In this case the equation is
x^2 + 8x + 22= 0


a=1\\b=8\\c =22\\\\((b)/(2))^2 = ((8)/(2))^2 = 16

3) Add 16 on both sides of equality


10(x^2 + 8x + 16) +220= 16*10

4) Factor the expression into parentheses and simplify


10(x+4)^2 +220= 16*10


10(x+4)^2= 16*10-220


10(x+4)^2 =-60


(x+4)^2 =-6

User Vincenza
by
6.3k points